Telejornalismo: diferentes reconfigurações da notícia - Backes, Vanessa Cristina (2018)
This research proposes to examine how news broadcasters aired by television stations may present different approaches of the same event throughout their programming. Thus, your goal is to examine not only the required attributes in order for an event to receive the status of news, but also the multiple discursive strategies employed to reconfigure this event in every news broadcast, giving it features of originality, specialty, and singularity. The analysis uses a methodology inspired by principles of European Semiotics based on Saussere, Hjelmslev, Greimas, and other researchers whose studies direct to the description of the televisual production. The corpus of this research consists of emissions from five news broadcasters aired daily by Rede Globo de Televisão: Hora 1, Bom Dia Brasil, Jornal Hoje, Jornal Nacional and Jornal da Globo, in order to examine what news they reconfigure and to demonstrate discursive strategies used in the process of replication. Among the main results obtained in the development of the theoretical methodological path already described, three different dynamics of re-presentation of the same facts / events in different editions of television news stand out: 1) the addition of narrative elements, comparing the first emission in relation to the following ; 2) the reconfiguration of the same discursive elements in all the analyzed narratives; and 3) the reprise of the same news conformation in different editions of news programs. The present research also raises hypotheses about the justifications for such dynamics of re - presentation of facts / events in different editions of RGT 's news programs.